A Concise Guide to Market Research The Process, Data, and Methods Using IBM SPSS Statistics - Sarstedt, Marko; Mooi, Erik.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This accessible, practice-oriented, and compact text provides a hands-on introduction to market research. Using the market research process as a framework, it explains how to collect and describe data and presents the most important and frequently used quantitative analysis techniques, such as ANOVA, regression analysis, factor analysis, and cluster analysis. The book describes the theoretical choices a market researcher has to make with regard to each technique, discusses how these are converted into actions in IBM SPSS version 22, and how to interpret the output. Each chapter concludes with a case study that illustrates the process using real-world data. A comprehensive Web appendix includes additional analysis techniques, datasets, video files, and case studies. Tags in the text allow readers to quickly access Web content with their mobile device. The new edition features: Stronger emphasis on the gathering and analysis of secondary data (e.g., internet and social networking data) New material on data description (e.g., outlier detection and missing value analysis) Improved use of educational elements such as learning objectives, keywords, self-assessment tests, case studies, and much more Streamlined and simplified coverage of the data analysis techniques with more rules-of-thumb Uses IBM SPSS version 22
Preface -- 1 Introduction to Market Research -- 2 The Market Research Process -- 3 Data -- 4 Getting Data -- 5 Descriptive Statistics -- 6 Hypothesis Testing & ANOVA -- 7 Regression Analysis -- 8 Factor Analysis -- 9 Cluster Analysis -- Index.
Keywords: Economics; Economics -- Statistics; Industrial management; Marketing; Economics/Management Science; Marketing; Management/Business for Professionals; Statistics for Business/Economics/Mathematical Finance/Insurance.